Factors Associated with Marginal Status among Patients with Colorectal Cancer Undergoing Colorectal Resection with Curative Intent at Muhimbili National Hospital (Tanzania Medical Journal, 2025)
Background: Colorectal carcinoma is the third most diagnosed cancer globally and the second leading cause of death. It is the most common gastrointestinal malignancy. Its incidence increases with economic growth. Surgical resection, with or without adjuvant therapy, is the primary treatment.Aim: To determine factors influencing surgical outcomes among patients with colorectal cancer undergoing colorectal resection for curative intent at Muhimbili National Hospital (MNH).Methodology: A prospective cross-sectional study design was conducted from October 2022 to April 2023 and included all patients with colorectal cancer who had undergone colorectal surgery for curative intent at MNH. Demographic data, clinical presentation of the illness, treatment given before surgery, surgical procedure detail was collected using a structured questionnaire and checklist. Surgical outcomes such as resection margins status, surgical site infection, reoperation, and mortality were assessed within one-month post-operation. Data were analyzed using STATA, where measures of central tendency and frequency distributions were found and associations of variables were done by bivariate and multivariate analysis.Results: A total of 139 patients were recruited. Of these, 75 were female (54.0%), and the mean age was 53.3±14.6. The overall rate of positive resection margins was 19.4%. Circumferential margins were positive in 13.7% of cases, distal margins in 7.2%, and proximal margins in 2.9%. Morbidity occurred in 30% of patients. This was defined as surgical site infections, peritonitis, intestinal obstruction, or acute kidney injury. The mortality rate was 10.8%. Patients who did not receive neoadjuvant therapy were 6.1 times more likely to have positive resection margins (OR 6.1). Positive microscopic nodal status was strongly associated with positive resection margins, with a 12.9-fold higher likelihood (OR 12.9) compared to negative nodal status. After adjusting for confounders, only microscopic nodal status and neoadjuvant therapy remained significantly associated with resection margin status. Patients with positive nodal status had an 11.6 times higher likelihood (OR 11.6) of positive resection margins. Those not receiving neoadjuvant therapy had a 5.6 times higher likelihood (OR 5.6).Conclusion: Positive nodal status and omission of neoadjuvant therapy are strong predictors of positive resection margins in colorectal cancer surgery at our center. Challenges in achieving clear circumferential margins highlight the need for more precise surgical techniques and advanced perioperative care.